The Effect of Social Interaction Patterns on Job Satisfaction - Nasyirudin, Muhammad; Fawazi, Muhammad Halim; Fitria, Desi (IJBLE Scientific Publications Community Inc., 2025)
In the context of small and medium enterprises (SMEs), social interaction patterns constitute a critical determinant of organizational dynamics and employee well-being. This study investigates the influence of social interaction patterns on employee job satisfaction at UD Anisa Jaya Kanigoro, Blitar Regency. Employing a quantitative associative approach with simple linear regression analysis, the research utilized a total sample of 10 permanent employees as respondents. Data were collected through validated Likert-scale questionnaires (Cronbach's Alpha: X=0.699; Y=0.831) and analyzed using SPSS. The findings reveal a significant positive influence of social interaction patterns on job satisfaction (t=3.610; p=0.007; β=0.787), with the regression equation Y=-0.984+0.951X indicating that each unit increase in social interaction patterns enhances job satisfaction by 0.951 units. The strength of influence reaching 78.7% demonstrates that relational dimensions dominate over structural factors in SME contexts. Management should prioritize social capital investment through systematic team-building programs, open communication forums, and strengthening reciprocity norms. Future research requires sample expansion and exploration of moderating variables to understand the boundary conditions of this relationship.